HUBUNGAN BURNOUT DENGAN KEPUASAN KERJA DALAM KALANGAN PEKERJA DI PEJABAT PERTUBUHAN KESELAMATAN SOSIAL (PERKESO) BATU PAHAT, JOHOR - Shaban, Siti Haziqah; Isahak, Nur Hadirah (Jurnal ’Ulwan, 2023)
The burnout factor with job satisfaction is very important to every working individual because an employee who is satisfied with his job will be more productive and give a high commitment to his job. Therefore, this study aims to investigate the relationship between burnout and job satisfaction among employees in PERKESO Batu Pahat, Johor. The respondents of this study consisted of 32 employees at the PERKESO Batu Pahat, Johor. The questionnaires used in this study were the Maslach Burnout Inventory (MBI) and the Minnesota Satisfaction Questionnaire (MSQ). The data obtained were processed using Statistical Package for the Social Science (SPSS) version 26 to evaluate the frequency percentage, correlation coefficient, t test and Anova. The results of the study found that there was no significant relationship between burnout and job satisfaction (r = .134, k> .05). The results also found that there was a significant difference in burnout based on gender (t = 4.303, k .05). In conclusion, several parties need to work together to help the workers to reduce this problem in order to produce quality workers.